Effects of hydrodynamic factors on Pecten maximus larval development. (27th April 2017) - Holbach, Marine; Robert, René; Miner, Philippe; Mingant, Christian; Boudry, Pierre; Tremblay, Réjean
Abstract: Hatchery production of great scallop, Pecten maximus, remains unpredictable, notably due to poor larval survival. Large‐scale flow‐through systems up to 3500 L have been developed to avoid the use of antibiotics in static systems. Alternatively, small‐scale flow‐through systems have been successfully applied for oysters but they proved to be unsuitable to rear scallop larvae. By focusing on physical factors presumed to limit P. maximus larval development, this study aimed to optimize great scallop larvae rearing parameters under controlled conditions. First, the influence of aeration on larval performances, energetic metabolism and antioxidant defences were studied both in static and flow‐through systems. Aeration depressed larval food intake, regardless of the intensities of flow tested (100 ml/min, 155 ml/min and 270 ml/min). On the other hand, antioxidant enzyme activities remained constant or decreased, suggesting that antioxidant defences were inactivated. The increase in citrate synthase activity suggested an increase in metabolic rate possibly due to a turbulent stressful environment. All larvae exposed to such turbulence died before reaching metamorphosis, whereas those reared without aeration survived well (≈ 95%). The effects of water renewal were thereafter studied in 50‐L flow‐through flat‐bottomed tanks. No differences in survival (20.4 ± 0.5%), growth (3.8 ± 0.2 μm/d), competence (5.6 ± 0.2%), energetic metabolism level and antioxidant enzyme activities were observed when comparing 12.5 and 25 L/hr water renewal. Whereas air bubbling leads to detrimental effects, flow‐through in small flat‐bottomed tanks appears to be a suitable technique for scallop larvae rearing.